2021
DOI: 10.1007/s10266-021-00674-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a familial cleidocranial dysplasia with a novel RUNX2 mutation and establishment of patient-derived induced pluripotent stem cells

Abstract: Cleidocranial dysplasia (CCD) is an autosomal dominant hereditary disease associated with the gene RUNX2. Disease-specific induced pluripotent stem cells (iPSCs) have emerged as a useful resource to further study human hereditary diseases such as CCD. In this study, we identified a novel CCD-specific RUNX2 mutation and established iPSCs with this mutation. Biopsies were obtained from familial CCD patients and mutation analyses were performed through Sanger sequencing and next generation sequencing. CCD-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A single supernumerary tooth (68.2%) was the most common, followed by 2 ST (31.2%), 3 ST (0.3%) and 4 ST (0.2%). Multiple ST (≥ 5 ST) are very rare and are usually associated with a syndrome, such as cleidocranial dysplasia [ 6 ]. A similar study was reported by Bereket, and the results suggested that 77.4% of patients had one supernumerary tooth, 18.4% of patients had 2 ST, and 4.2% of patients had 3 or more ST [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single supernumerary tooth (68.2%) was the most common, followed by 2 ST (31.2%), 3 ST (0.3%) and 4 ST (0.2%). Multiple ST (≥ 5 ST) are very rare and are usually associated with a syndrome, such as cleidocranial dysplasia [ 6 ]. A similar study was reported by Bereket, and the results suggested that 77.4% of patients had one supernumerary tooth, 18.4% of patients had 2 ST, and 4.2% of patients had 3 or more ST [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several scientific hypotheses have been put forward to explain the aetiology and development of ST including atavism, dichotomy of the tooth bud, hyperactivity of the dental lamina, and genetic factors [ 5 ]. It has been reported that genetics and heredity play a key role in the occurrence of ST, especially in patients with a syndrome or family history [ 6 ]. Environmental factors will increase individual genetic susceptibility [ 7 ].…”
Section: Introductionmentioning
confidence: 99%